Pengaruh Kinerja Keuangan terhadap Financial Distress dengan Komisaris Independen sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Vinny Avie Nadia; Fitra Dharma (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
This study examines the effect of financial performance on financial distress, with independent commissioners as a moderating variable, among state-owned enterprises listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Financial distress is measured using the Altman Z-Score Type 3 method. The independent variables are financial performance, consisting of profitability ratios (NPM), liquidity ratios (CR), and leverage ratios (DER), as well as independent commissioners as a moderating variable. This study employs a quantitative approach using purposive sampling, resulting in a sample of 14 companies with 54 observations after outlier removal. Data analysis was performed using multiple regression and moderation regression via SPSS 26. The results indicate that Profitability and Liquidity have a significant negative effect, while Leverage has no significant effect on financial distress. The relationship between Profitability and Liquidity and financial distress is not strengthened by Independent Commissioners, but Independent Commissioners do weaken the relationship between Leverage and financial distress.